Religious Freedom: Freedom of Conversion or Freedom from Conversion? - John, Aruthuckal Varughese (International bulletin of mission research, 2021)
The orthodox Hindu objection to the classic formulation of religious freedom, as seen in the UN Universal Declaration of Human Rights and other charters, is with the Judeo-Christian origin or bias in these secular frameworks. It argues that in the application of laws protecting religious freedom, the secular framework erroneously presupposes a similarity between Semitic religions and Hinduism. Consequently, the secular framework applies Judeo-Christian anthropological assumptions that favor conversionary religions, which function against the interests of Asiatic religions.